Disparities in Colorectal Cancer Incidence Trends Among Hispanics Living in Puerto Rico (2000–2021): A Comparison With Surveillance, Epidemiology, and End Results (SEER) Database - Luis D. Borrero‐Garcia; Marilyn Moró‐Carrión; Carlos R. Torres‐Cintrón; Hilmaris Centeno‐Girona; Victoria Perez; Taymaraliz Santos‐Colón; María González‐Pons (Cancer Medicine)
ABSTRACT Background Although the overall colorectal cancer (CRC) incidence has been steadily declining in the United States, a dramatic increase in the number of CRC cases among individuals younger than 50 years of age (early‐onset CRC) has been observed. CRC is the second and first leading cause of cancer death in the United States and among Hispanic men and women living in Puerto Rico (PRH), respectively. We report CRC incidence rates from 2000 to 2021 among PRH and compare them to data in the Surveillance, Epidemiology, and End Results Program (SEER). Methods Data on colorectal adenocarcinomas diagnosed between January 1, 2000, and December 31, 2021, were obtained from the Puerto Rico Central Cancer Registry and SEER17, including race and ethnicity. Age‐standardized incidence rates were calculated using the direct method. The Joinpoint Regression Program calculated temporal trends on CRC incidence rates based on age‐adjusted Average Annual Percent Change (AAPC) estimates. Results A total of 729,479 incident cases of CRC were analyzed. US Hispanics had the highest percentage of early‐onset CRC (EOCRC) cases (17.0%) among the racial and ethnic groups studied. PRH had the highest age‐standardized EOCRC incidence rate (12.18 per 100,000 persons) and the highest increase in EOCRC incidence temporal trends (AAPC = 2.68; 95% CI: 1.83 to 3.51). Conclusions A significantly higher increase in EOCRC incidence was observed among Hispanic populations. Future studies should disaggregate Hispanic subpopulations by considering the country of ancestral origin, which will help identify specific risk factors and exposures and aid in developing tailored prevention and risk stratification strategies to reduce EOCRC incidence.